Strategic Management in Blood Donation Activities: Increasing Participation and Positive Impact - Wahyu Akbar, Tri Sanatha; Raspati, Galih; Wijaya, Zeffanya Raphael; Wiyata, Mariati Tirta (Jurnal Empathy Pengabdian Kepada Masyarakat, 2026)
Background: Ensuring an adequate blood supply remains a persistent public health challenge, particularly in developing regions. In Bandung City, Indonesia, the daily demand for blood reaches approximately 500 units, while supply remains limited to 200–300 units due to low public awareness and insufficient donor participation. Addressing this gap requires not only awareness campaigns but also structured managerial approaches. This study aims to examine the effectiveness of applying strategic management principles to enhance participation and awareness in community-based blood donation programs. Methods: This study adopted a structured community service design integrating strategic management stages: planning, socialization, implementation, and evaluation. The intervention involved educational sessions delivered by management academics and PMI practitioners, covering donor motivation, health benefits, and strategic organization of social programs. The training was conducted over a four-hour session. Program effectiveness was assessed using a pre-test and post-test approach to measure changes in participants’ knowledge and awareness. Results: The program successfully collected 63 blood units, exceeding the initial target of 50 units. Quantitative findings indicate a significant improvement in participants’ knowledge and awareness, with an average increase of 32% following the intervention. These results demonstrate that integrating strategic management into community service activities can substantially improve participation outcomes. Conclusion: The findings highlight the critical role of strategic management in enhancing the effectiveness of blood donation initiatives. This approach provides a scalable and replicable model for improving donor participation and ensuring sustainable blood supply in resource-constrained settings.